Evaluation of Surface Roughness of ST-60 Steel Material After Turning Process With Variation of Rotation - Herlambang, Bambang (Piston: Journal of Technical Engineering, 2025)
It is necessary to select the right material, set the right machine, and determine the optimal machining parameters to obtain the best quality product. In the lathe process, surface roughness is a very important factor and is the main indicator in assessing the quality of the workpiece. Surface roughness can be used to evaluate whether the workpiece meets quality standards or not. The lower the surface roughness value on the workpiece, the better the quality. Conversely, a high surface roughness value can have a negative impact on the performance of the workpiece mating components, because it increases friction on the machine elements that are in contact with each other. This study aims to determine the effect of variations in spindle rotation, feed speed, and feed depth on the level of surface roughness resulting from the lathe machining process. In addition, this study also aims to identify which factors contribute the most to achieving optimal surface roughness in the lathe machining process. The samples to be used is steel ST-60 with a diameter of 22 mm and a length of 120 mm in the form of a solid cylinder. The lathe machine to be used is Conventional Milling Machine equipped with Rotary Table, Dividing Head and Machine Clamp. The samples was turned at cutting depth 0,5 mm with rotation 140, 280, 560, 1.120 Rpm and feeding length 5 cm. The experiment was conducted with three repetitions on each combination of variables to ensure the accuracy of the data obtained. Surface roughness measurements were carried out horizontally on the surface of the workpiece by taking three times the data on each workpiece. The results show that the smoothest surface is achieved at low rotation speed 140 Rpm with Ra value 1.140 µm and the highest value of Ra is 2.690 µm at 560 Rpm. This is due to at low speeds in the turning process helps reduce excess cutting forces, heat, tool wear, and vibration, resulting in smoother surfaces.